Population and distribution of some herons in Babakan Rancabayawak, Bandung City, Indonesia - Erri Noviar Megantara; Teguh Husodo; Johan Iskandar; Deden Nurjaman; Suroso SUROSO; SYAHRAS FATHIN AMINUDDIN; Zamzam I'lanul Anwar Atsaury; Indri Wulandari; Sya Sya Shanida (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Megantara EN, Husodo T, Iskandar J, Nurjaman D, Suroso, Aminuddin SF, Atsaury ZIA, Wulandari I, Shanida SS. 2021. Population and distribution of some herons in Babakan Rancabayawak, Bandung City, Indonesia. Biodiversitas 22: 5389-5396. The Cinambo River flood control channel in the Rancabayawak impacts the decline in the habitat quality of some herons, such as cattle egret [Bubulcus ibis (Linnaeus, 1758)], little egret [Egretta garzetta (Linnaeus, 1766)], and Javan pond-heron [Ardeola speciosa (Horsfield, 1821)]. Besides, many built-up areas due to the urbanization in peri-urban areas also impact habitat quality, such as the loss of plants commonly used as perching and nesting sites. Along with the development of Rancabayawak as a built-up area, it is essential to study the management of those birds. This study aims to reveal: 1) plants used as perching and nesting sites, 2) population size and distribution, and management efforts on B. ibis, E. garzetta, and A. speciosa in Babakan Rancabayawak Hamlet, Gedebage Subdistrict, Bandung, West Java, Indonesia. A mixed-methods approach was applied in this study by calculating the estimated population and bird nests, plant inventory survey, and the installation of the A8 mini GPS. Bambusa vulgaris, Leucaena leucocephala, and Mimosa pigra are plants that are used as perching and nesting sites by B. ibis, E. garzetta, and A. speciosa. The estimated population mean of those birds was 630 individuals, 92 individuals, and 43 individuals, respectively, with the population average of those birds, is 1680 individuals. Three hundred twenty-nine nests (329) were found during the study. Based on distribution mapping, birds moved east and south, covering paddy fields in Rancaekek, Solokanjeruk, and Majalaya within a radius of 12 km. Management efforts can be conducted by not cutting down the plants that become nesting and perching sites and maintaining the wetlands in their habitats.